ANALISIS PERAN VISUAL BASIC DALAM MENINGKATKAN PRODUKTIVITAS ADMINISTRASIPERKANTORAN - alli, alli gufron albani; AKBAR RIVADLY, ZIKRY; NURUL FAMELA, DINI; ABELIA SYAHMAR, ZABRINA; RAMLAN, ADILA (JURNAL DATA SAINS DAN TEKNOLOGI INFORMASI (DASTIS), 2025)
This study evaluates the impact of a Visual Basic (VB)-based administrative system on office productivity, focusing on time efficiency, data accuracy, and administrative workload. Using a quasi-experimental pretest-posttest design, the results show significant improvements in administrative efficiency, reduced processing time, fewer errors, and more streamlined workflows after system implementation. The importance of incremental development is also emphasized, allowing system refinement based on user feedback. These findings enrich the literature on office automation with empirical evidence that VB can enhance productivity, speed up processes, reduce errors, and simplify administrative tasks. Future research could explore the long-term impact and cost-benefit analysis of implementing this technology. The practical implication is that organizations can improve their administrative efficiency by implementing VB-based automation systems.